UUM engaged in partnership with leading universities in Thailand - New Sarawak, Tribune (New Sarawak Tribune, 2015)
ALOR SETAR: In an effort to empower the internationalisation agenda and strengthening the transformation plan of University Utara Malaysia (UUM), a delegation headed by vice chancellor Prof Datuk Dr Mohamed Mustafa Ishak has visited five leading universities in Thailand.